2019
DOI: 10.3389/fpls.2019.01565
|View full text |Cite
|
Sign up to set email alerts
|

Floral Color, Anthocyanin Synthesis Gene Expression and Control in Cape Erica Species

Abstract: Introduction: The Cape Floristic Region (CFR) is a biodiversity hotspot, recognized globally for its unusually high levels of endemism. The origins of this biodiversity are a long-standing topic of research. The largest “Cape clade,” Erica, radiated dramatically in the CFR, its ca. 690 species arising within 10–15 Ma. Notable between- and within-species flower color variation in Erica may have contributed to the origins of species diversity through its impact on pollinator efficiency and specificity.Methods: W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 44 publications
1
11
1
Order By: Relevance
“…4 c). As an important step in the anthocyanin biosynthetic pathway, DFR is associated with anthocyanin colouration in flowers, such as Freesia hybrida [ 54 ], Andean genus Iochroma (Solanaceae) [ 55 ] and Cape Erica species [ 56 ]. In the present study, four DFR genes were identified and increased from WF_Pe to YF_Pe.…”
Section: Discussionmentioning
confidence: 99%
“…4 c). As an important step in the anthocyanin biosynthetic pathway, DFR is associated with anthocyanin colouration in flowers, such as Freesia hybrida [ 54 ], Andean genus Iochroma (Solanaceae) [ 55 ] and Cape Erica species [ 56 ]. In the present study, four DFR genes were identified and increased from WF_Pe to YF_Pe.…”
Section: Discussionmentioning
confidence: 99%
“…In theory, the transition from pigmented to white flowers could involve any mutations that block one or more steps in the anthocyanin pathway. This includes loss-of-function mutations in any pathway enzyme-coding genes, as well as the cis-regulatory genes that influence any of the pathway enzymes [34,35]. In our study, expression analysis identified several obvious differentially expressed genes in the petal which were down-regulated in white samples compared to pigmented samples, but metabolite detection found that Cy-and Del-derivatives existed in both white petals and pigmented petals, indicating that the color variations, especially the white petals, do not lacking any steps of the anthocyanin pathway.…”
Section: Discussionmentioning
confidence: 99%
“…4c). As an important step in the anthocyanin biosynthetic pathway, DFR is associated with anthocyanin colouration in owers, such as Freesia hybrida [52], Andean genus Iochroma (Solanaceae) [53] and Cape Erica species [54]. In the present study, four DFR genes were identi ed and increased from WF_Pe to YF_Pe.…”
Section: Pigment Accumulation and Metabolism-related Genesmentioning
confidence: 49%